Novel microdeletions on chromosome 14q32.2 suggest a potential role for non-coding RNAs in Kagami-Ogata syndrome - van der Werf, Ilse M (Eur J Hum Genet, 2016)
In approximately 20% of individuals with Kagami-Ogata syndrome (KOS14, MIM 608149), characterized by a bell-shaped thorax with coat-hanger configuration of the ribs, joint contractures, abdominal wall defects and polyhydramnios during the pregnancy, the syndrome is caused by a maternal deletion of the imprinted gene cluster in chromosome 14q32.2. Most deletions reported so far included one or both of the differentially methylated regions (DMRs) – DLK1/MEG3 IG-DMR and MEG3-DMR. We present two unrelated families with two affected siblings each, presenting with classical KOS14 due to maternally inherited microdeletions. Interestingly, all four patients have lived through to adulthood, even though mortality rates for patients with KOS14 due to a microdeletion are relatively high. In the first family, none of the DMRs is included in the deletion and the methylation status is identical to that of controls. Deletions that do not encompass the DMRs in this region are thus sufficient to elicit the full KOS14 phenotype. In the second family, a partially overlapping deletion including both DMRs and MEG3 was detected. In summary, we show that patients with KOS14 can live into adulthood, that causal deletions do not have to include the DMRs and that consequently a normal methylation pattern does not exclude KOS14.